2012
DOI: 10.3382/ps.2012-02370
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary probiotic (Pediococcus acidilactici) supplementation on performance, nutrient digestibility, egg traits, egg yolk cholesterol, and fatty acid profile in laying hens

Abstract: The objective of this study was to determine the effect of dietary probiotic Pediococcus acidilactici (PA) strain MA18/5M on performance, egg traits, egg cholesterol content, and fatty acid composition in laying hens during a 24-wk period. A total of 222 Hy-Line Brown laying hens, 22 wk of age, were divided into 3 treatment groups. Control group (C) hens were fed a basal diet with no probiotic added. In group PA1, the basal diet was supplemented with PA at 100 mg.kg(-1) of feed for the first 12 wk and 50 mg.kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
71
2
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(91 citation statements)
references
References 43 publications
12
71
2
6
Order By: Relevance
“…Moreover, the egg concentrations of vitamin A, crude fat, vitamin E, calcium, zinc, selenium, and dry matter also dramatically improved in the eggs of yeastfed hens (Table 5). Similar studies reported a significant improvement of egg production in hens fed a mixed culture of probiotics, such as Lactobacillus acidophilus and Lactobacillus casei (Tortuero & Fernandez, 1995), L. acidophilus alone , Pediococcus acidilactici (Mikulski et al, 2012), Bacillus subtilis (Xu et al 2006;Abdelqader et al 2013), Propionibacterium jensenii (Luo et al, 2010), and Saccharomyces cerevisiae (Yalçin et al, 2010). Significant improvements in egg weight and eggshell quality were also obtained in hens fed diets supplemented with a mixture of Lactobacillus cultures (Davis & Anderson, 2002;Kalavathy et al, 2009).…”
Section: Effects Of Kluyveromyces Marxianus Isolated From Tibetan Musmentioning
confidence: 77%
“…Moreover, the egg concentrations of vitamin A, crude fat, vitamin E, calcium, zinc, selenium, and dry matter also dramatically improved in the eggs of yeastfed hens (Table 5). Similar studies reported a significant improvement of egg production in hens fed a mixed culture of probiotics, such as Lactobacillus acidophilus and Lactobacillus casei (Tortuero & Fernandez, 1995), L. acidophilus alone , Pediococcus acidilactici (Mikulski et al, 2012), Bacillus subtilis (Xu et al 2006;Abdelqader et al 2013), Propionibacterium jensenii (Luo et al, 2010), and Saccharomyces cerevisiae (Yalçin et al, 2010). Significant improvements in egg weight and eggshell quality were also obtained in hens fed diets supplemented with a mixture of Lactobacillus cultures (Davis & Anderson, 2002;Kalavathy et al, 2009).…”
Section: Effects Of Kluyveromyces Marxianus Isolated From Tibetan Musmentioning
confidence: 77%
“…However, there were no significant differences in yolk cholesterol observed among all dietary treatment groups during the later laying period at 32 and 36 wk of age (Table ). The egg yolk cholesterol content was also found to be lowered by 13.68% in hens fed inulin (Shang and others ), 11.97% in hens fed fructooligosaccharide (Li and others ), 11.47% in hens fed probiotic Pediococcus acidilactici (Mikulski and others ), and 9.9% in hens fed a multi‐strain probiotic (Aghaii and others ). The discrepancies in results could be due to differences in prebiotics, probiotic strains, administration doses, and hen ages and strains.…”
Section: Resultsmentioning
confidence: 95%
“…The addition of probiotics to the diets of laying hens has been found to improve egg quality parameters including egg shell thickness (Panda and others ; Abdelqader and others ), egg specific gravity, and albumen quality (Haugh unit) (Khan and others ). Probiotic supplementation may also alter the lipid metabolism of chickens as several studies have indicated that probiotics could reduce the cholesterol content of egg yolks (Kurtoglu and others ; Kalavathy and others ; Mikulski and others ), sera (Kurtoglu and others ), and carcasses (Kalavathy and others ) of laying hens and broiler chickens.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in Ca and Zn contents in yolk may be due to the hypothesis that an acidic environment created in the digestive tract by AA and LAB facilitates the ionisation of minerals and improves their absorption (Haddadin et al 1996). Mikulski et al (2012) found that increasing in Ca retention in hens fed probiotic-supplemented diets.…”
Section: Egg Yolk Fatty Acid Profile and Minerals Contentmentioning
confidence: 99%